Myeloid-derived growth factor protects against pressure overload-induced heart failure by preserving sarco/endoplasmic reticulum Ca2+-ATPase expression in cardiomyocytes - Korf, Mortimer; Reboll, Marc R.; Polten, Felix; Weber, Natalie; Jäckle, Felix; Wu, Xuekun; Kallikourdis, Marinos; Kunderfranco, Paolo; Condorelli, Gianluigi; Giannitsis, Evangelos; Kustikova, Olga S.; Schambach, Axel; et al. (Circulation, 2021)
Background: - - Inflammation contributes to the pathogenesis of heart failure, but there is limited understanding of inflammation’s potential benefits. Inflammatory cells secrete MYDGF (myeloid-derived growth factor) to promote tissue repair after acute myocardial infarction. We hypothesized that MYDGF has a role in cardiac adaptation to persistent pressure overload. - - Methods: - - We defined the cellular sources and function of MYDGF in wild-type (WT), Mydgf-deficient (Mydgf−/−), and Mydgf bone marrow-chimeric or bone marrow-conditional transgenic mice with pressure overload-induced heart failure after transverse aortic constriction surgery. We measured MYDGF plasma concentrations by targeted liquid chromatography-mass spectrometry. We identified MYDGF signaling targets by phosphoproteomics and substrate-based kinase activity inference. We recorded Ca2+ transients and sarcomere contractions in isolated cardiomyocytes. Additionally, we explored the therapeutic potential of recombinant MYDGF. - - Results: - - MYDGF protein abundance increased in the left ventricular myocardium and in blood plasma of pressure-overloaded mice. Patients with severe aortic stenosis also had elevated MYDGF plasma concentrations, which declined after transcatheter aortic valve implantation. Monocytes and macrophages emerged as the main MYDGF sources in the pressure-overloaded murine heart. While Mydgf−/− mice had no apparent phenotype at baseline, they developed more severe left ventricular hypertrophy and contractile dysfunction during pressure overload than WT mice. Conversely, conditional transgenic overexpression of MYDGF in bone marrow-derived inflammatory cells attenuated pressure overload-induced hypertrophy and dysfunction. Mechanistically, MYDGF inhibited G protein-coupled receptor agonist-induced hypertrophy and augmented SERCA2a (sarco/endoplasmic reticulum Ca2+-ATPase 2a) expression in cultured neonatal rat ventricular cardiomyocytes by enhancing PIM1 (Pim-1 proto-oncogene, serine/threonine kinase) expression and activity. Along this line, cardiomyocytes from pressure-overloaded Mydgf−/− mice displayed reduced PIM1 and SERCA2a expression, greater hypertrophy, and impaired Ca2+ cycling and sarcomere function compared with cardiomyocytes from pressure-overloaded WT mice. Transplanting Mydgf−/− mice with WT bone marrow cells augmented cardiac PIM1 and SERCA2a levels and ameliorated pressure overload-induced hypertrophy and dysfunction. Pressure-overloaded Mydgf−/− mice were similarly rescued by adenoviral Serca2a gene transfer. Treating pressure-overloaded WT mice subcutaneously with recombinant MYDGF enhanced SERCA2a expression, attenuated left ventricular hypertrophy and dysfunction, and improved survival. - - Conclusions: - - These findings establish a MYDGF-based adaptive crosstalk between inflammatory cells and cardiomyocytes that protects against pressure overload-induced heart failure.
Im Text ist "2+" hochgestellt
Gesehen am 24.12.2021